Maqāsid al-Shariʿah and Digital Forensics: Towards a Fiqh-Based Evidentiary Model in Sharīʿah Criminal Justice - Tuan Muhammad Faris Hamzi Tuan Ibrahim; Nasrul Hisyam Nor Muhamad; Ahmad Syukran Baharuddin (Universitas Islam Negeri Raden Intan Lampung, 2025)
The development of the form and modus operandi of sharīʿah crimes in Malaysia has exposed the weaknesses of the traditional Sharīʿah evidentiary framework. The absence of physical evidence in crimes committed in the digital environment makes reliance on digital evidence a necessity. Accordingly, the objective of this study is to examine the need and legal validity of integrating digital forensic evidence in Sharīʿah criminal proceedings, with a particular focus on taʿzīr offences, based on the role of maqāṣid al-sharīʿah. This qualitative research uses document analysis as its main method. Inductive and deductive methods were used for qualitative content analysis. The maqāṣid al-sharīʿah framework was then applied to assess whether digital forensic methods conform to the rules of Sharīʿah evidence. If digital evidence meets legal standards for validity, suitability, and proper procedures, it is accepted in Sharīʿah cases. Using digital evidence within the maqāṣid al-sharīʿah framework can improve Islamic proof methods and show how fiqh adapts to new technology-based crimes. The study concludes that merging digital forensics with the maqāṣid al-sharīʿah is urgent to develop a fiqh-based evidence model and help Sharīʿah Courts follow Islamic doctrine while addressing new crime trends